Review of micro propulsion technology for space gravitational waves detection. (April 2022) - Liu, Hui; Niu, Xiang; Zeng, Ming; Wang, Shangsheng; Cui, Kai; Yu, Daren
Abstract: Gravitational Wave (GW) signal was first detected by Advanced Laser Interferometer Gravitational-Wave Observatory (aLIGO) in 2005 making GW detection a hotspot. The low-frequency gravitational signal needs to be detected in space. As the actuator of the drag-free control system, the micro propulsion system works to provide a super-stable platform for satellites by offsetting non-conservative forces. In this paper, some micro propulsion systems are analyzed from their work mechanisms and task requirements to justify suitability for space GWs detection. According to the analysis results, recent progress for cold gas propulsion, wave ionization ion propulsion, Hall propulsion and field emission effect electric propulsion (FEEEP) are introduced in detail. Lastly, the future of micro propulsion for space GWs detection is analyzed from engineering respects. Graphical abstract: The cusped magnetic field confines electrons by magnetic mirror effect. It means electrons would be exerted a force illustrated as equation (11), dragging them when they move to some regions with stronger magnetic field. Therefore, electrons are dragged when they move to the magnetic cusp and confined by this way. Most electrons can be confined between two magnetic cusps and the others can cross magnetic cusp by Bohm condition and near wall condition. The magnetic configuration can decrease the interaction between plasma and wall, prolong thruster lifetime and enhance discharge stability when the thruster is adjusted in large range [67]. Highlights: Analysis the requirements and the root of difficulties of micro propulsion system for space GWs detection. Analysis the feasibility of micro propulsion systems for space GWs detection from their mechanism. Sort out four micro propulsion systems potential for space GWs detection and introduce their recent progress.